Geomorphology; Geochronology; São Francisco river; Northeast of Brazil. / Geological and geomorphological characterization of the State Park of Ibitipoca, MG (Brazil): ground for the understanding of its geopatrimony - Lilian Carla Moreira Bento; Sílvio Carlos Rodrigues (Sociedade & Natureza)
The State Park of Ibitipoca (PEI) is a state conservation unit most visited in the state of Minas Gerais,according to data from State Forest Institute (IEF, 2012) and these statistics reflect the great scenic beautyof its geopatrimony, such as caves, waterfalls, river beaches, stone bridge, etc. The objective of this studyis to make the local geological and morphological characterization so that one can understand the existinggeopatrimony there. One hopes that the information made available here may be, in the future, adaptedand passed on to the park visitors, promoting not only the contemplation, but also the understanding ofgeopatrimony, under the perspective of valuing this aspect of nature.